Glucose 6 phosphate dehydrogenase deficiency and hemoglobinopathy in South Western Region Nepal: a boon or burden - Narayan Gautam; Bhagwati Gaire; Trishna Manandhar; Bishnu P. Marasini; Niranjan Parajuli; Sunil P. Lekhak; Monica Nepal (BMC Research Notes, 2019)
Abstract Objectives The study was carried out to optimize the phenotypic method to characterize the sickle cell trait (SCT), sickle cell anemia (SCA), and β-thalassemia (β-TT) suspected sample from tharu community of South Western province-5, Nepal. SCT and SCA were further evaluated by genotypic method employing amplification refractory mutation system (ARMS PCR). Moreover, Glucose 6 phosphate dehydrogenase (G6PD) was estimated in those hemoglobinopathy to observe its prevalence. The accurate and reliable method can play an important role in reduction of morbidity and mortality rate. Results The 100 suspected cases were subjected to phenotypic method adopting cellulose acetate electrophoresis and genotypic method using ARMS PCR which portraits (5%) SCA positive test showing HBS/HBS, (38%) SCT positive trait HBA/HBS and (36%) cases normal HBA/HBA. β-TT (21%) cases were confirmed by electropherogram. G6PD deficiency was observed in (40%) of SCA, (18.4%) of SCT, (4.8%) of β-TT and (2.8%) in normal cases. Increased G6PD were developed only in SCT (5.3%) and β-TT (4.8%). The study highlighted sickle cell disorder (SCD) and β-TT as the most common hemoglobinopathy coexisting with G6PD deficiency. Though hemoglobinopathy sometime could be protective in malaria but G6PD deficiency can cause massive hemolysis which may exacerbate the condition.